Bridging Voices. Embracing Translanguaging for Emergent Bilingual Students - Pawliszko, Judyta (Wydawnictwo Uniwersytetu Rzeszowskiego, 2026)
This book situates emergent bilinguals within the evolving educational landscape, highlighting the limitations of monolingual approaches and offering translanguaging classrooms as an inclusive and empowering alternative. It introduces transpositioning and co-learning as innovative frameworks that foster dynamic, reciprocal relationships between students and educators. These methodologies challenge monolingual ideologies and address the cognitive and socio-emotional dimensions of bilingual identity formation. Drawing on case studies, teacher reflections, and research data, the book provides practical strategies to address systemic inequities and equips educators with tools for fostering inclusive learning environment. By positioning translanguaging as a critical framework for multilingual literacy, academic engagement, and social justice, this work advances the discourse on linguistic equity and transformative pedagogy.

Książka przedstawia uczniów bilingwalnych w kontekście współczesnych przemian edukacyjnych, wskazując ograniczenia podejść monolingwalnych oraz proponując translanguaging jako inkluzyjną i wzmacniającą alternatywę dydaktyczną. Publikacja wprowadza pojęcia transpozycjonowania oraz współuczenia się jako innowacyjne ramy wspierające dynamiczne i wzajemne relacje pomiędzy uczniami a nauczycielami. Podejścia te podważają monolingwalne ideologie oraz odnoszą się do poznawczych i społeczno-emocjonalnych aspektów kształtowania tożsamości bilingwalnej. Opierając się na studiach przypadków, refleksjach nauczycieli oraz danych badawczych, książka prezentuje praktyczne strategie przeciwdziałania nierównościom systemowym oraz wyposaża nauczycieli w narzędzia służące budowaniu inkluzywnego środowiska edukacyjnego. Ukazując translanguaging jako istotne narzędzie wspierające alfabetyzację wielojęzyczną, zaangażowanie akademickie oraz sprawiedliwość społeczną, publikacja wnosi wkład do dyskusji nad równością językową i transformacyjną pedagogiką.
Keywords: Keywords: translanguaging; emergent bilinguals; EBs; home language; inclusion; co-learning; transpositioning; translanguaging; uczniowie bilingwalni; edukacja wielojęzyczna; język ojczysty; edukacja włączająca; współuczenie się; transpozycjonowanie